Las carretas del vino: tráfico y fletes en el san juan de la frontera en el reino de chile (siglo XVII) - Rivera Medina, Ana María; Fanchín, Ana (Revista de Historia Social y de las Mentalidades, 2011)
The present article analyzes the infrastructure of the transport that is generated from San Juan around the wine production along the XVII cent ury. During these dates, it was consolidating the commercial traffic of the Cuyo’s wines toward the Counties of the East and North of the current Argentinean territory . For its elaboration we have used documental funds, unpublished until this moment, ma inly the sources corresponding to the XVII century of the General File of San Juan’s County.